3 Idiots: Exploring Innovative Marketing - Upadhyay, Nidhi (Indian Journal of Marketing, 2010)
Every business tries to stay upfront with their customers. The free market scenario has brought a situation that is characterized by cutthroat competition. We live in a world that is ruled by "survival of the fittest" policy. The race to be ahead has resulted in companies coming up with new and innovative marketing strategies to gain a competitive edge over their competitors.